2005
DOI: 10.1038/ni1171
|View full text |Cite|
|
Sign up to set email alerts
|

A cytosolic pathway for MHC class II–restricted antigen processing that is proteasome and TAP dependent

Abstract: By convention, presentation of major histocompatibility complex (MHC) class I-restricted epitopes involves processing by cytosolic proteasomes, whereas MHC class II-restricted epitopes are generated by endosomal proteases. Here, we show that two MHC class II-restricted epitopes within influenza virus were generated by a proteasome- and TAP-dependent pathway that was accessed by exogenous virus in dendritic cells (DCs) but not cell types with less permeable endosomes. Both epitopes were presented by recycling M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 50 publications
7
151
2
Order By: Relevance
“…These results suggest that HSPA might chaperone peptides from the proteasome to TPPII, if necessary, and to the TAP complex which would then convey the peptides into the ER. In a very similar manner, the HLA class II antigen presentation of endogenous epitopes might be handled by HSPA since it has been shown that endogenous class II epitopes are proteasomeand TAP-dependent (Mukherjee et al 2001;Tewari et al 2005). In fact, two peptides co-purified with HSPA, K15 and K20, were matched to HLA class II epitopes (Table 4), which consequently suggests that HLA class II epitopes may be chaperoned by HSPA.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results suggest that HSPA might chaperone peptides from the proteasome to TPPII, if necessary, and to the TAP complex which would then convey the peptides into the ER. In a very similar manner, the HLA class II antigen presentation of endogenous epitopes might be handled by HSPA since it has been shown that endogenous class II epitopes are proteasomeand TAP-dependent (Mukherjee et al 2001;Tewari et al 2005). In fact, two peptides co-purified with HSPA, K15 and K20, were matched to HLA class II epitopes (Table 4), which consequently suggests that HLA class II epitopes may be chaperoned by HSPA.…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, it has been suggested that particular HSPs are involved in the antigen presentation process. The endogenous and exogenous (TAP-dependent) antigen generation for HLA class I presentation, as well as the generation of endogenous HLA class II epitopes, depends on the proteasome (Kovacsovics-Bankowski and Rock 1995; Mukherjee et al 2001;Norbury et al 2004;Tewari et al 2005). Peptides produced by the proteasome are prone to rapid degradation in the cell (Fruci et al 2003;Princiotta et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…25 In certain APCs like DCs, this pathway is even accessed by exogenous antigens like influenza HA and neuraminidase, which leave the endosome for proteasome-and TAP-dependent processing onto MHC class II. 46 A third pathway involves processing of cytosolic or nuclear proteins (e.g. glutamate decarboxylase 65 (GAD65) 33 ) by the proteasome and is TAP independent.…”
Section: Endogenous Mhc Class II Processingmentioning
confidence: 99%
“…Two different pathways have been implicated in the processing of these antigens, with one pathway involving the cytoplasmic proteasome [7][8][9] and another involving autophagy [5,[10][11][12]. As an example of a proteasome-dependent pathway, the presentation by HLA-DR4 of the endogenous protein glutamate decarboxylase, a C 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.eji-journal.eu Eur.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the presentation of antigenic peptides derived from exogenous proteins by MHC class II molecules is relatively well understood [1]. Several biochemical studies have revealed that a large fraction of naturally processed peptides presented by MHC II molecules are derived from endogenous cytoplasmic and nuclear proteins [2][3][4][5][6].Two different pathways have been implicated in the processing of these antigens, with one pathway involving the cytoplasmic proteasome [7][8][9] and another involving autophagy [5,[10][11][12]. As an example of a proteasome-dependent pathway, the presentation by HLA-DR4 of the endogenous protein glutamate decarboxylase, a C 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.eji-journal.eu Eur.…”
mentioning
confidence: 99%